IDIOMATIC EXPRESSION IN UMPAMA PAKPAK WEDDING CEREMONY - Aguni Berutu and Juli Rachmadani Hsb (LINGUISTICA, 2017)
This study deals with idiomatic expression in Pakpak wedding ceremony. The objectives of this study were to find out the categories of umpama, to describe the meaning of umpama, and to find out the dominant category of umpama used in Pakpak wedding ceremony. This research was conducted by using descriptive qualitative design. The data were 25 utterances of idiomatic expression (umpama)  taken from Pakpak wedding ceremony records. The findings indicated that there were three categories of umpama Pakpak, they were: umpama related to flora, fauna, and daily activities. The total percentages of umpama for each category were: related to flora (52%), fauna (8%), and daily activities (16%), while not categorized (24%). The meaning of umpama in Pakpak wedding ceremony were containing wishes, hopes, prayers, and advices. The dominant category was related to flora (52%).